From Concept to Action: Stories of Gender and Climate Change - Global Gender and Climate Alliance (2015)
The case study focuses on CCAFS CSVs in Nyando, Kenya and the approaches the initiative has taken to reach women -- through SMS and the kinds of technologies they have adopted, e.g. drip irrigation).